VB.NET core classes in a nutshell : a desktop quick reference - Kurniawan, Budi.; Neward, Ted. (Beijing : O'Reilly, 2002)
This sequel to VB .NET Language in a Nutshell covers the key classes in the .NET framework using Visual Basic syntax. It is aimed at programmers who want a quick introduction to Base Class Library .
Includes index.
Keywords: BASIC (Computer program language).; Microsoft .NET Framework; Visual Basic